Prevalence and factors associated with teenage pregnancy in Sierra Leone: evidence from a nationally representative Demographic and Health Survey of 2019 - Lilian Nuwabaine; Quraish Sserwanja; Kassim Kamara; Milton W. Musaba (BMC, 2023)
Abstract Background Globally, teenage pregnancy remains a public health concern because of the associated maternal and perinatal morbidity and mortality. To address the extensive social, political and economic effects of teenage pregnancy, there is need for current epidemiological evidence on its prevalence and associated factors, especially from low resource settings where the burden is highest. Methods We used data from the 2019 Sierra Leone Demographic and Health Survey (SLDH), which included 3,427 female adolescents. Multistage stratified sampling was used to select study participants. Teenage pregnancy was defined as those who had ever either had a child, or terminated a pregnancy, or were currently pregnant. Multivariable logistic regression was conducted to determine the factors associated with teenage pregnancy using SPSS version 25(Armonk, NY: IBM Corp). Results The prevalence of teenage pregnancy was 22.1% [758/3,427]. Of these, 17.8%, (608/3427), had ever had childbirth, 4.2%, (144/3427), were pregnant, and 1.2%, (40/3427) had ever terminated a pregnancy. After adjusting for confounders, the odds of teenage pregnancy among married girls were about 15 times more than the odds among those who were not married (aOR; 15.31, 95% CI: 11.17-20.98) while the odds of teenage pregnancy among girls from the poorest households were 2.5 times more than the odds among girls from the richest households. Conclusion The prevalence of teenage pregnancy in Sierra Leone is high. To reduce teenage pregnancy, the government of Sierra Leone and its partners should target married, older teenagers and those from poor households. Policies giving teenage mothers a second chance by encouraging them to return to school after childbirth should be encouraged as an alternative to early marriages.